Egg & spoon a novel - Maguire, Gregory 1954- (Candlewick Press, 2014)
In 1905 czarist Russia, an impoverished country girl Elena and the aristocratic Ekatrina meet and set in motion an escapade that includes mistaken identity, a monk locked in a tower, a prince traveling incognito, and the witch Baba Yaga
Keywords: Mistaken identity; Monks; Princes; Witches; Baba Yaga (Legendary character); Russland; Russia; Jugendbuch